Providing English Village Training for Students and Boat Rowers at Rammang-Rammang World Geopark Tourism - Rina Asrini Bakri; Saiful Saiful; St Asriati Am; Hamid Ismail; Ibrahim H Ahmad (STAI Hubbulwathan Duri, 2023)
This study aims to provide English Village training for high school students and boat rowers at Rammang-Rammang World Geopark Tourism. This activity is expected to attract the enthusiasm of students and boat rowers to learn English as a foreign language. The researchers conducted a study in Salenrang Rammang-Rammang Maros Village. The population of this study amounted to 98 people, consisting of 20 high school students and 78 boat rowers. The cluster sampling technique was used in selecting samples with prior knowledge of English so that only 33 were selected as respondents, namely 20 high school students and 13 boat rowers. The instrument used by researchers in this study is a questionnaire. Questionnaires are used to collect information about current conditions, identify respondents' needs in learning English in English Village and find out the problems encountered in speaking. The results reported that 33 respondents expressed enthusiasm to welcome the program, and they were well motivated to join the training. They were also happy to empower English language training because English is essential to their work as boat rowers. The same goes for the students because they can increase their knowledge of English in addition to what they get from school.